Building trust, resilient regions, and educational narratives: Municipalities dealing with COVID-19 in border regions of Portugal. (September 2021) - Marques da Silva, Sofia
This article recounts how municipalities from border regions in mainland Portugal interacted with the population in the face of the new social order brought about by COVID-19. Our aim is to interpret new educational spaces, beyond schools, emerging from community-level strategies to build trust during the pandemic lockdown and state of emergency. The material consists of 1503 posts from 38 Facebook pages of municipalities that were analysed and organised into dimensions: health and COVID-19; offline to online adaptation strategies; cross-border impact information; economic encouragement; care and social support; community engagement and participation. The article focuses on this last dimension given its pre-eminence. Key findings manifested five educational narratives associated with community engagement and participation: past and memory; place; voicing and wisdom; recognition and solidarity; and participation and learning. We consider those narratives as community resilience builders, accounting for municipalities' educational strategies that enhanced locally anchored responses. If those actions represent an opportunity for local-governing new protagonism, they also generate a footprint for encouraging transformative resilience grounded in situated literacies and new educational audiences. Municipalities were more than timely information providers – they invested in connecting with the population, an investment possibly explained by the awareness that a health crisis could easily morph into a social crisis.